2017
DOI: 10.15406/mojbb.2017.03.00030
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive Microspheres of Chitosan and Polyvinyl Alcohol as A Carrier for Intranasal Delivery of Insulin: In Vitro and In Vivo Studies

Abstract: The aim of this study was to investigate the capabilities of chitosan microspheres as drug carrier system in co-formulation with polyvinyl alcohol (PVA), to improve the systemic absorption of intranasal insulin delivery.Insulin loaded microspheres was developed from varying ratio of chitosan solutions along with polyvinyl alcohol (PVA) as additive polymer using spray drying method. Different formulations were developed and morphological studies of the optimized formulas showed that the size range of spherical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…according to the method described by Freshney 26 Results are expressed in percentage. All compounds except [17] b and [17] d showed more than 50% inhibition for mice intestines carcinoma cell line, while these compounds [17] b and [17] d exhibit inhibition more than 50% inhibition for human pelvic rhabdomyosarcoma.…”
Section: Anticancer Activitymentioning
confidence: 92%
See 2 more Smart Citations
“…according to the method described by Freshney 26 Results are expressed in percentage. All compounds except [17] b and [17] d showed more than 50% inhibition for mice intestines carcinoma cell line, while these compounds [17] b and [17] d exhibit inhibition more than 50% inhibition for human pelvic rhabdomyosarcoma.…”
Section: Anticancer Activitymentioning
confidence: 92%
“…PVA is a semi-crystalline polymer containing crystalline and amorphous phase 17 which is used in biomedical and pharmaceutical applications 18 and in industries due to the excellent chemical and physical properties, non-toxicity, good chemical resistance, good film formation capacity. 19 It has been applied in production of many end products, as lacquers, resins, surgical threads , and food packaging materials 20 .…”
Section: This Is Anmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that slow release was achieved via the PVA-CS network. In 2017, a similar study was conducted to evaluate the potential of PVA-CS microspheres as a vehicle for insulin drug delivery via intranasal administration [ 84 ]. The authors developed different formulations, and morphological analysis of the optimized formulas showed that the size range was between 200 nm to 2 µm.…”
Section: Applications Of Pva-cs Hydrogelmentioning
confidence: 99%
“…The authors developed different formulations, and morphological analysis of the optimized formulas showed that the size range was between 200 nm to 2 µm. The in vitro study showed that microspheres from PVA-CS exhibited immediate, sharp, and erratic drug release, while the in vivo investigation in rats demonstrated a reduced drug release rate and better mucoadhesive properties [ 84 ]. Thus, using PVA-CS in drug delivery systems produced favorable outcomes.…”
Section: Applications Of Pva-cs Hydrogelmentioning
confidence: 99%